A functional wound dressing as a potential treatment for cutaneous leishmaniasis - Alexandrino-Junior, Francisco; E Silva, Kattya Gyselle de Holanda; Freire, Marjorie Caroline Liberato Cavalcanti; Lione, Viviane de Oliveira Freitas; Cardoso, Elisama Azevedo; Marcelino, Henrique Rodrigues; Genre, Julieta; de Oliveira, Anselmo Gomes [UNESP]; Do Egito, Eryvaldo Sócrates Tabosa (MDPI, 2019)
Cutaneous leishmaniasis (CL) is a parasitic disease characterized by progressive skin sores. Currently, treatments for CL are limited to parenteral administration of the drug, which presents severe adverse effects and low cure rates. Therefore, this study aimed to develop poly(vinyl-alcohol) (PVA) hydrogels containing Amphotericin B (AmB) intended for topical treatment of CL. Hydrogels were evaluated in vitro for their potential to eliminate promastigote forms of Leishmania spp., to prevent secondary infections, to maintain appropriate healing conditions, and to offer suitable biocompatibility. AmB was incorporated into the system in its non-crystalline state, allowing it to swell more and faster than the system without the drug. Furthermore, the AmB release profile showed a continuous and controlled behavior following Higuchi´s kinetic model. AmB-loaded-PVA-hydrogels (PVA–AmB) also showed efficient antifungal and leishmanicidal activity, no cytotoxic potential for VERO cells, microbial impermeability and water vapor permeability compatible with the healthy skin’s physiological needs. Indeed, these results revealed the potential of PVA–AmB to prevent secondary infections and to maintain a favorable environment for the healing process. Hence, these results suggest that PVA–AmB could be a suitable and efficient new therapeutic approach for the topical treatment of CL.
Keywords: Amphotericin B; Controlled release; Cutaneous leishmaniasis; Hydrogel; Wound dressing